2005
DOI: 10.1021/bi047687a
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Equilibrium Unfolding of Triosephosphate Isomerase from Trypanosoma cruzi in Guanidinium Hydrochloride Involves Stable Dimeric and Monomeric Intermediates

Abstract: The reversible guanidinium hydrochloride-induced unfolding of Trypanosoma cruzi triosephosphate isomerase (TcTIM) was characterized under equilibrium conditions. The catalytic activity was followed as a native homodimeric functional probe. Circular dichroism, intrinsic fluorescence, and size-exclusion chromatography were used as secondary, tertiary, and quaternary structural probes, respectively. The change in ANS fluorescence intensity with increasing denaturant concentrations was also determined. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 67 publications
5
37
0
Order By: Relevance
“…However, this result is consistent with that of several other dimeric proteins including factor for inversion stimulation protein, 50 the ATPase SecA, 72 organophosphorus hydrolase, 73 triosephosphate isomerase 74,75 and glutathione reductase 76 where a dimeric intermediate has been observed. Like apo-S100B, each of these proteins has the appearance of a transition corresponding to a F 2 ⇄ I 2 step at relatively low GuHCl concentrations (b 2 M), indicative that the dissociation of the dimer is a less favourable process.…”
Section: Discussionsupporting
confidence: 87%
“…However, this result is consistent with that of several other dimeric proteins including factor for inversion stimulation protein, 50 the ATPase SecA, 72 organophosphorus hydrolase, 73 triosephosphate isomerase 74,75 and glutathione reductase 76 where a dimeric intermediate has been observed. Like apo-S100B, each of these proteins has the appearance of a transition corresponding to a F 2 ⇄ I 2 step at relatively low GuHCl concentrations (b 2 M), indicative that the dissociation of the dimer is a less favourable process.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple unfolded states have been reported in the case of glutathione transferase (14). Reversible equilibrium of unfolding of triophosphate isomerase from Trypanosoma cruzi in Gdn-HCl has been reported (15). Irreversible unfolding of a-amylase was analysed by unfolding kinetics.…”
Section: Effect Of Gdn-hcl At Different Temperaturesmentioning
confidence: 99%
“…Regarding protein folding studies with homologous proteins, in the early reports it was reported that the folding pattern is conserved trough evolution; however, in the literature different folding pathways for homologous proteins with the same denaturant condition have been reported. In this context, TIM is one of the most studied proteins (3). The oligomeric nature of TIM has been analyzed on enzymes mainly from mesophile organisms, where it is always a homodimeric protein, being the simplest model of oligomerization.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the denaturation reaction is reversible, while in others, unspecific irreversible aggregation appears. For some species, the unfolding model is described by a two-state transition (24,(35)(36)(37)(38), while in others, more complex processes, including intermediates, have been observed (3,32,(39)(40)(41)(42)(43). These intermediates are responsible for the aggregation and irreversibility observed during unfolding experiments in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation